Endometrial cancer: correlation of apparent diffusion coefficient (ADC) with tumor cellularity and tumor grade. (August 2016) - Kishimoto, Keiko; Tajima, Shinya; Maeda, Ichiro; Takagi, Masayuki; Ueno, Takahiko; Suzuki, Nao; Nakajima, Yasuo
Background: Diffusion-weighted imaging (DWI) and the apparent diffusion coefficient (ADC) are widely used for detecting uterine endometrial cancer. The relationships between ADC values and pathological features of endometrial cancer have not yet been established. Purpose: To investigate whether ADC values of endometrial cancer vary according to histologic tumor cellularity and tumor grade. Material and Methods: We retrospectively reviewed 30 pathologically confirmed endometrial cancers. All patients underwent conventional non-enhanced magnetic resonance imaging (MRI) and DWI procedures, and ADC values were calculated. Tumor cellularity was evaluated by counting cancer cells in three high-power ( × 400) fields. The correlation between ADC values and tumor cellularity was assessed using Pearson's correlation coefficient test for statistical analysis. Results: The mean ± standard deviation (SD) ADC value ( ×10 −3 mm 2 /s) of endometrial cancer was 0.85 ± 0.22 (range, 0.55–1.71). The mean ± SD tumor cellularity was 528.36 ± 16.89 (range, 298.0–763.6). ADC values were significantly inversely correlated with tumor cellularity. No significant relationship was observed between ADC values and tumor grade (mean ADC values: G1, 0.88 ± 0.265 × 10 −3 mm 2 /s; G2, 0.80 ± 0.178 × 10 −3 mm 2 /s; G3, 0.81 ± 0.117 × 10 −3 mm 2 /s). Conclusion: There is a significant inverse relationship between ADC values and tumor cellularity in endometrial cancer. No significant differences in average ADC value were observed between G1, G2, and G3 tumors. However, the lower the tumor grade, the wider the SD.